2018
DOI: 10.1021/acsbiomaterials.8b00850
|View full text |Cite
|
Sign up to set email alerts
|

Autonomously Oscillating Hydrogel Microspheres with High-Frequency Swelling/Deswelling and Dispersing/Flocculating Oscillations

Abstract: Fast swelling/deswelling and dispersing/flocculating oscillations of autonomously oscillating hydrogel microspheres (microgels) at periods of single-order seconds were accomplished. The design of the oscillating microgels is based on the incorporation of neutral and hydrophilic acrylamide monomers into conventional microgels to suppress the irreversible aggregation of the microgels during oscillation at high substrate concentrations and high temperatures in the Belousov–Zhabotinsky (BZ) reaction. In contrast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…Functional molecules including drugs and proteins can diffuse into the microgel interior for later release in response to the environment. Thus, microgels are attractive for use in the human body. , Because of their fascinating properties, which combine the features of hydrogels and colloids, microgels are expected to find use in numerous applications, including molecular separation, , catalysts, , biosensors, , emulsifiers, , actuators, and model systems for cells, glasses, , and crystals. , …”
Section: Introductionmentioning
confidence: 99%
“…Functional molecules including drugs and proteins can diffuse into the microgel interior for later release in response to the environment. Thus, microgels are attractive for use in the human body. , Because of their fascinating properties, which combine the features of hydrogels and colloids, microgels are expected to find use in numerous applications, including molecular separation, , catalysts, , biosensors, , emulsifiers, , actuators, and model systems for cells, glasses, , and crystals. , …”
Section: Introductionmentioning
confidence: 99%
“…Based on same strategy, the Suzuki group further developed an oscillating microgel system which exhibited fast swelling/deswelling and dispersing/flocculating oscillation. 437 They suggested that this system could be explored in fabricating autonomously oscillating micropumps similar to human heartbeat. Ballav and co-workers undertook a similar strategy to convert a coordination polymer gel into a conducting polymer gel.…”
Section: (Iii) Redox Responsive Self-regulating Gel To Gel Transitionsmentioning
confidence: 99%
“…Due to their desirable properties, microgels have found applications, not only in a dispersed state, for example as carriers for drug-delivery systems, [5][6][7] in molecular separations, [8][9][10][11] and in functional catalysts, [12][13][14] but also in assembled states, for example as cell scaffolds, 15,16 sensors, 17,18 emulsi-ers, 19,20 and actuators. [21][22][23] The rst reported microgels were thermoresponsive poly(Nisopropyl acrylamide) (pNIPAm)-based microgels cross-linked with N,N 0 -methylenebis(acrylamide) (BIS). 24 These microgels have a volume-phase-transition temperature (VPTT) of $32 C and their physicochemical properties change quickly when the temperature increases beyond this point.…”
Section: Introductionmentioning
confidence: 99%